(untitled) (Confluenţe Bibliologice, 2025)
The text is dedicated to the date of opening to the public more than 120 years ago one of the most popular world famous art museums The State Tretyakov Gallery in Moscow. The founder of the art Gallery was Pavel Tretyakov, successful businessman, famous philanthropist and great humanist. And even in the beginning of the 21st century his name is forever associated with sincerely love to painting and devotion to his native country.